163k views
5 votes
Combine like terms to create an equivalent expression.

1/7-3(3/7n-2/7)

User Bhaxy
by
5.6k points

2 Answers

3 votes

Answer:

The answer is 1-9/7n

Explanation:

This is what it is on khan academy.

User Susie Humby
by
5.9k points
5 votes

Answer:

The equivalent expression is n = 9/7

Explanation:

Combining like terms and simplifying, we have:

1/7 -3 (3/7n-2/7)

1/7 - 9/7n + 6/7

7/7 - 9/7n

1 - 9/7n

7n - 9 (Multiplying both terms by 7n)

7n - 9 = 0

7n = 9

n = 9/7

The equivalent expression is n = 9/7

User Alex Godofsky
by
6.3k points